2018
DOI: 10.1007/s13193-018-0836-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of Poor Oral Hygiene in Causation of Oral Cancer—a Review of Literature

Abstract: Oral squamous cell carcinomas (OSCC) are among the commonest cancers in South East Asia and more so in the Indian subcontinent. The role of tobacco and alcohol in the causation of these cancers is well-documented. Poor oral hygiene (POH) is often seen to co-exist in patients with OSCC. However, the role of poor oral hygiene in the etio-pathogenesis of these cancers is controversial. We decided to evaluate the available literature for evaluating the association of POH with OSCC. A thorough literature search of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 71 publications
0
16
0
1
Order By: Relevance
“…Other factors such as inflammation of gingival/periodontal, genetic variation, salivary dysfunction, dietary habits, and smoking can also lead to oral dysbiosis. [35][36][37] This review identified the various oral microbiota among oral cancer patients. The three major phyla (Firmicutes, Bacteroidetes, and Proteobacteria) were the most prevalent bacterial found in oral cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors such as inflammation of gingival/periodontal, genetic variation, salivary dysfunction, dietary habits, and smoking can also lead to oral dysbiosis. [35][36][37] This review identified the various oral microbiota among oral cancer patients. The three major phyla (Firmicutes, Bacteroidetes, and Proteobacteria) were the most prevalent bacterial found in oral cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…They consider factors such as the oral hygiene index, the presence of halitosis, the number of missing teeth, brushing techniques used, the usage of mouthwash and so on. As a result, according to a study conducted in India on 337 people diagnosed with oral cancer, around 79 percent of them have poor oral hygiene [ 30 ]. Individuals’ cleanliness habits must be identified, as well as their motivation to maintain the greatest dental-periodontal status, as part of the screening required to get an early diagnosis of malignant tumor proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol consumption, smoking, chronic mucosal irritation/trauma, and poor oral hygiene are considered risk factors for oral cancer [1][2][3][4][5]. Regarding the carcinogenicity of alcohol, the International Agency for Research on Cancer (IARC) classified alcoholic beverages into group 1 (carcinogenic to humans), since ethanol can be metabolized to acetaldehyde, a strong carcinogen [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%